Marc-doa for cognitive and psychomotor learning: preliminary design and evaluation / Hendra Pradibta and Usman Nurhasan - Pradibta, Hendra; Nurhasan, Usman (UiTM Cawangan Perlis, 2021)
Marc-doa application is Mobile Augmented Reality cubes used as a learning media for children, focusing on cognitive and psychomotor learning. The contents of this application are daily prayers for Muslim children and designed in the form of audio-video animations. The development of the Marc-doa application uses the Multimedia Development Life Cycle method. This research aims to discuss the design and evaluation of Marc-doa. Evaluation and technical tests are conducted on several aspects, specifically on the detection process, distance, angle, and surface area. In addition, the testing process is to identify the ideal conditions for the use of Marc-doa. From the evaluation and testing process, four markers showed good results. Only one marker does not show the results as expected. The ideal distance for using Marc-doa application between 25-40 cm. The angle for ideal reception between 0-30 degrees and the surface area Marc-doa application can detect markers correctly between 50%-100% surface area. The ideal distance, surface area, and conditions for utilising Marc-doa application were obtained from this research.